THE IMPACT OF SOCIOPRAMATIC OF RECEIPT PATTERN IN ENGLISH ARTS TEXTS - Asst. Lect. Ali Gomar Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Sociopragmatics conducts studies to understand the cross-cultural diversity among different nations, as a respect of verbal and non-verbal elements. The different perceptions aspects of the target culture in order to minimize intercultural factors hindering of our research language proficiency to enable ourselves interpret culturally accepted folklore, gestures, sounds, and the use of space and time correctly. Our recent research explain many valuable things like aims at highlighting the importance of sociopragmatic elements such as idioms, proverbs, politeness norms, and more; as well as paralinguistics, kinesics, and proxemics in our problem of the research.